Defining venous thromboembolism and measuring its incidence using Swedish health registries: a nationwide pregnancy cohort study - Abdul Sultan, Alyshah; West, Joe; Stephansson, Olof; Grainge, Matthew J.; Tata, Laila J.; Fleming, Kate M.; Humes, David; Ludvigsson, Jonas F. (BMJ Publishing Group Ltd, 2015)
Objective: To accurately define venous thromboembolism (VTE) in the routinely collected Swedish health registers and quantify its incidence in and around pregnancy. Study design: Cohort study using data from the Swedish Medical Birth Registry (MBR) linked to the National Patient Registry (NPR) and the Swedish Prescribed Drug Register (PDR). Setting: Secondary care centres, Sweden. Participant: 509 198 women aged 15–44 years who had one or more pregnancies resulting in a live birth or stillbirth between 2005 and 2011. Main outcome measure: To estimate the incidence rate (IR) of VTE in and around pregnancy using various VTE definitions allowing direct comparison with other countries. Results: The rate of VTE varied based on the VTE definition. We found that 43% of cases first recorded as outpatient were not accompanied by anticoagulant prescriptions, whereas this proportion was much lower than those cases first recorded in the inpatient register (9%). Using our most inclusive VTE definition, we observed higher rates of VTE compared with previously published data using similar methodology. These reduced by 31% (IR=142/100 000 person-years; 95% CI 132 to 153) and 22% (IR=331/100 000 person-years; 95% CI 304 to 361) during the antepartum and postpartum periods, respectively, using a restrictive VTE definition that required anticoagulant prescriptions associated with diagnosis, which were more in line with the existing literature. Conclusions: We found that including VTE codes without treatment confirmation risks the inclusion of false-positive cases. When defining VTE using the NPR, anticoagulant prescription information should therefore be considered particularly for cases recorded in an outpatient setting.